Participatory Scenario Planning (PSP) coordination meeting: Consultations and agreed actions - Koech, Grace; Otieno, Felix; Gamoyo, Majambo; Wahome, Anastasia; Kinyua, Ivy; Ogutu, Liz; Ghosh, Aniruddha (2024)
Climate change poses significant challenges to livelihoods in Africa, particularly affecting vulnerable communities reliant on rainfall for agriculture. This unpredictability threatens food security hindering national development. Participatory Scenario Planning (PSP) offers a collaborative approach to climate information services, co-producing actionable weather and climate information. In Kenya, PSP initiatives have grown but face challenges of duplication and resource inefficiencies. To address this, the Alliance of Bioversity and CIAT convened A PSP coordination workshop bringing together diverse stakeholders to streamline PSP efforts. The primary objective was to find ways to ensure the coordinated dissemination of climate information among stakeholders. Recommendations focus on establishing a national technical working group, conducting regular coordination meetings, synthesizing outcomes, engaging missing stakeholders, integrating PSP into national plans, enhancing capacity building, implementing robust monitoring and evaluation, and exploring sustainable funding mechanisms. These actions aim to strengthen PSP coordination, improve climate resilience, and support informed decision-making across Kenya's diverse regions.